Mathematical Modeling of Stenosis in the Carotid Bifurcation as a Cause of Ischemic Stroke - Fatahillah, Arif; Adani, Dzawawi Dimas; Adawiyah, Robiatul; Setiawani , Susi; Prihandini, Rafiantika Megahnia; Baskonus, Haci Mehmet (Statistics, Optimization & Information Computing, 2025)
Ischemic stroke is the most common type of stroke, caused by disrupted blood flow to the brain. This study aims to analyze blood flow stenosis in the carotid bifurcation, a major cause of ischemic stroke. A mathematical model is developed using the finite volume method, considering variations in shape, thickness, and stenosis location. The stenosis shapes analyzed include bell-shaped, cosine-shaped, and elliptical, with narrowing levels of 60%, 70%, 80%, and 90%. The mathematical model is solved using the SIMPLE algorithm and simulated in Python to assess the impact of stenosis on ischemic stroke risk. The simulation provides velocity and pressure data across different stenosis shapes and thicknesses, enabling a comprehensive risk analysis. Computational Fluid Dynamics (CFD) is employed to simulate turbulent flow in the carotid bifurcation using ANSYS FLUENT. The findings indicate that 90% stenosis in the carotid bifurcation poses a significant risk, as the resulting flow velocity and pressure exceed normal thresholds. This study provides valuable insights into the effects of carotid bifurcation stenosis on ischemic stroke occurrence and its implications.